Analisis Penyebab Utama Kerusakan Suara pada Speaker dengan Menggunakan Metode Fishbone Diagram dan FMEA - Sakti, Yuni Krida (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Speaker damage consists of sound damage and appearance damage. Most speaker product defects are due to sound damage, so this greatly affects the quality of the speaker. The voice damage that has the largest percentage is the VCT (Voice Coil Touch) type of damage at 47.6% compared to appearance damage which only reaches 1.6%. This research aims to determine the main cause of VCT damage using the FMEA (Failure Mode and Effect Analysis) method, so it can be seen that the main cause is human factors with the type of failure in installing a slanted voice coil with the highest RPN (Risk Priority Numbers) value of 216.